2009
DOI: 10.1002/ijc.24744
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of the heterogeneous nuclear ribonucleoprotein K in pancreatic cancer and its association with the mutant p53

Abstract: The heterogeneous nuclear ribonucleoprotein (hnRNP) K is an essential RNA and DNA binding protein involved in gene expression and signal transduction including DNA transcription, RNA splicing, RNA stability and translation. The role of hnRNP K in cancer is relatively understudied. However, several cellular functions strongly indicate that hnRNP K is involved in tumorigenesis. In this study, we investigated the altered protein expression and the subcellular distribution of the hnRNP K protein using tissue micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
48
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 40 publications
8
48
0
2
Order By: Relevance
“…Together, these data suggest that hnRNPK can act as a tumor suppressor in hematological disorders. Conversely, hnRNPK was shown to be overexpressed in a variety of cancers, including breast, esophageal squamous cell, pancreatic, skin, colorectal, and oral squamous cell carcinoma (Mandal et al 2001;Carpenter et al 2006;Roychoudhury and Chaudhuri 2007;Zhou et al 2010). hnRNPK overexpression results in enhanced malignancy and metastasis in vitro, at least in part through alternative splicing of target genes that regulate the extracellular matrix, cell motility, and angiogenesis (Gao et al 2013).…”
Section: Hnrnpk-heterogeneous Nuclear Ribonucleoprotein Kmentioning
confidence: 99%
“…Together, these data suggest that hnRNPK can act as a tumor suppressor in hematological disorders. Conversely, hnRNPK was shown to be overexpressed in a variety of cancers, including breast, esophageal squamous cell, pancreatic, skin, colorectal, and oral squamous cell carcinoma (Mandal et al 2001;Carpenter et al 2006;Roychoudhury and Chaudhuri 2007;Zhou et al 2010). hnRNPK overexpression results in enhanced malignancy and metastasis in vitro, at least in part through alternative splicing of target genes that regulate the extracellular matrix, cell motility, and angiogenesis (Gao et al 2013).…”
Section: Hnrnpk-heterogeneous Nuclear Ribonucleoprotein Kmentioning
confidence: 99%
“…hnRNPK is the most widely studied, and its expression and the significance of its expression have been investigated in several types of cancer including colorectal cancer, prostate cancer, pancreatic cancer, oral cancer, nasopharyngeal cancer, and cervical cancer [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, 4IF4E transcription is up-regulated when both c-myc and hnRNPK are co-overexpressed [46], suggesting that hnRNPK may cooperate with additional oncoproteins which are permissive toward cancerous growth. In breast cancer cells [47], prostate carcinoma [48], and pancreatic cancer [49], plenty of researches demonstrated that hnRNPK significantly enhances the proliferative activity of tumor cells. Besides that, several research findings have confirmed that there is a close relation between hnRNPK and tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%